First Regional Super ESPC: Success on Kodiak Island, Alaska - Federal Energy Management Program (National Renewable Energy Laboratory (U.S.), 2001)
This case study about energy saving performance contacts (ESPCs) presents an overview of how the Coast Guard at Kodiak Island, Alaska, established an ESPC contract and the benefits derived from it. The Federal Energy Management Program instituted these special contracts to help federal agencies finance energy-saving projects at their facilities.